2021
DOI: 10.1111/jocn.16134
|View full text |Cite
|
Sign up to set email alerts
|

Chinese late‐life immigrants’ loneliness and social isolation in host countries: An integrative review

Abstract: Aims and objective To synthesise current international empirical evidence on loneliness and social isolation in Chinese late‐life immigrants. Background Loneliness causes adverse health consequences in Chinese late‐life immigrants leading to increased utilisation of often increasingly limited healthcare resources. However, little is known about how Chinese late‐life immigrants perceive and experience loneliness and social isolation in their host countries. Design An integrative review methodology. Methods Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
1
24
1
Order By: Relevance
“…The survey results showed a moderate level of overall loneliness in middle‐aged and older Chinese immigrants in New Zealand during the implementation of the COVID‐19 social distancing measures. The level of loneliness in this study was much higher than the loneliness of Chinese late‐life immigrants in New Zealand reported by a previous study 18 before the COVID‐19 pandemic, where the overall loneliness scores measured by the Chinese version 6‐item De Jong Gierveld Loneliness scale had a mean of 2.44. The COVID‐19 pandemic caused a so‐called ‘loneliness epidemic’ 19 internationally, representing an unspoken toll of COVID‐19.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The survey results showed a moderate level of overall loneliness in middle‐aged and older Chinese immigrants in New Zealand during the implementation of the COVID‐19 social distancing measures. The level of loneliness in this study was much higher than the loneliness of Chinese late‐life immigrants in New Zealand reported by a previous study 18 before the COVID‐19 pandemic, where the overall loneliness scores measured by the Chinese version 6‐item De Jong Gierveld Loneliness scale had a mean of 2.44. The COVID‐19 pandemic caused a so‐called ‘loneliness epidemic’ 19 internationally, representing an unspoken toll of COVID‐19.…”
Section: Discussioncontrasting
confidence: 80%
“… 26 However, fewer studies on robots have addressed the loneliness of older Chinese immigrants living in their own homes in the community. Studies on older Chinese immigrants’ lifestyle 27 and experience of loneliness 18 in New Zealand communities have revealed that some older Chinese immigrants reluctantly discarded prior customary filial piety expectations, in favour of external services/resources to support their care arrangements and to help them cope with loneliness. To fill the research gap, this study examined the association between loneliness and the acceptance of robots and pets among middle‐aged and older Chinese immigrants living in the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, loneliness is commonly reported by Chinese late-life immigrants when residing in host countries. 7 In addition, late-life immigrants from China, India, and Korea identified negative resettlement experiences and loneliness in New Zealand. 8 However, many studies on loneliness do not distinguish late-life immigrants from older adults who immigrated prior to reaching older adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…10 These issues are potential risks for loneliness of Chinese late-life immigrants as previously reported in Australia and Canada. 7 Further evidence is needed to understand the nuanced experiences of loneliness and the potential links between the disruption of traditional core values associated with filial piety and the experience of loneliness.…”
Section: Introductionmentioning
confidence: 99%